A literature review of corporate governance - Chen, Xue Yu (Edelweiss Applied Science and Technology, 2024)
Corporate governance is a set of rules, practices and laws that guide companies to operate in an ethical and responsible manner. In the process of corporate operations, shareholders and management make decisions and supervise through clear rules, procedures and structures. Modern corporate governance emphasizes separation of duties and effective supervision. The separation of duties within the company helps to prevent conflicts of interest and unethical behavior. Its core lies in the allocation of power and the coordination of interests, avoiding conflicts of interest between shareholders and management, thereby improving the financial performance and market competitiveness of the company. This article combs through a large number of corporate governance practice literature to find out the effectiveness of corporate governance mechanisms in companies and institutions. This article also looks at reducing agency problems through effective corporate governance mechanisms.